Design of Web-Based Journalist News Data Collection Application with Scrum Method - Rico Imanta Ginting; Andri Dwi Andhika (Jurnal Info Sains : Informatika dan Sains, 2026)
Analisatoday.com is a leading news portal focusing on political, economic and social issues. This portal aims to provide media solutions for public leaders and political figures in publicizing their activities and activities more effectively and professionally. By promoting the principles of transparency and information disclosure, Analisatoday.com plays an important role in delivering information about the work programs, visits, meetings, and activities of leaders to the public. In the process of news publication, the use of technology has grown, including in terms of data collection and information management. However, the news data collection system at Analisatoday.com is still not optimal. Currently, the data collection process is still mixed with news uploading activities, and is less efficient and not well organized. In addition, the lack of user understanding of the existing system is also an obstacle. To overcome these problems, the author designed a web-based journalist news data collection application using the Scrum method. This system is designed to be simpler, more efficient, and accurate in supporting the work process of journalists. Through this application, journalists can collect, verify, and manage news data in an integrated manner. With website-based technology and the utilization of PHP and MySQL as tools, this system is expected to improve  performance  and  effectiveness  in  managing  news  data  in Analisatoday.com.